Fundamental frequency and larynx height in sentence and stress groups - Reinholt Petersen, Niels (Annual Report of the Institute of Phonetics University of Copenhagen, 1985)
The paper reports experiments investigating a) the relation between larynx height and the slow overall fundamental frequency movement (declination) in sentences of varying length and type, and b) the relation between larynx height and Fo in the prosodic stress group. The aim of the experiments was to see in general to what extent the extrinsic laryngeal muscles could be assumed to be involved in the production of Fo, and as part of this to consider more specifically the question whether the fundamental frequency declination is actively controlled by the speaker in a linguistically purposeful manner, or whether - as has been suggested - it is an automatic consequence of the functioning of the pulmonic system. The results can be summarized as follows: In declarative sentences an overall decline was observed for Fo as well as for larynx height, and for both the slope of declination varied with sentence length, being steeper in short than in long sentences. In interrogative sentences Fo as well as larynx height showed either no decline or a slight rise over the sentence. These results are taken to indicate that Fo declination is actively controlled by the speaker, and it is suggested that it may be attributed primarily to the activity of the extrinsic laryngeal muscles. In the stress group the relation between larynx height and Fo seems to be far more complex, showing patterns which vary both among speakers and (to a lesser degree) within the individual speaker, and which have to be explained as the result of an intricate interaction of the activity of both intrinsic and extrinsic laryngeal muscles.